폴리카보네이트 소재의 자연폭로와 실내촉진 내후성 영향 - 문정미(Jung-mi Moon); 장호진(Ho-Jin Jang); 김창환(Chang-Hwan Kim) (Biuletyn Uniejowski, 2022)
Natural(outdoor) and accelerated(artificial) weathering tests were performed to investigate their influence on polycarbonate. The polycarbonate materials were prepared of various formulations divided into three batches, with existing, development materials1, development materials2, containing mixture of UV additives. Weathering tests were carried out as outdoor weathering(Seosan, South Korea) and accelerated weathering(xenon-arc), and the results analysis were evaluated based on yellow-index(YI), scanning electron microscope(SEM/EDS), energy dispersive x-ray spectroscopy(XRD), and gel permeation chromatography(GPC). Among the three materials, processing method development materials1 with UV stabilizer was excellent in weathering. This study can provide basic data for standardization of development and performance evaluation on livestock barn roof.